Empirisme et phénoménologie: Husserl et l’empirisme humien - Pradelle, Dominique (Bollettino Filosofico, 2024)
What position does English empiricism, especially Hume’s, occupy within the history of philosophy as conceived by Husserl? Did English empiricism anticipate the phenomenological problem of the transcendental constitution of objects by consciousness or, on the contrary, act as an epistemological obstacle by failing to recognize the intentional essence of consciousness? Leaving aside the question of Husserlian nominalism, we focus here on what Husserl calls his fictionalism, i.e. his theory of object identity as a fiction produced by the imagination. The contribution of Hume’s empiricism to transcendental phenomenology is to have thematized the field of cogitationes, where Descartes had concentrated on the evidence of the cogito alone, and to have posed the problem of the relation of consciousness to an external and permanent object. But his essential limitation is to have conceived this field on the model of material nature, and to have sought to provide a genetic explanation for the shared belief in the existence of external objects; in so doing, he misses the intentional essence of consciousness and the ideal status of the external thing. Keywords: Associationism, Constitution, Empiricism, Exteriority, Fictionalism, Imagination, Immanence, Intentionality, Permanence, Phenomenology